Direct in situ spectroscopic evidence of the crucial role played by surface oxygen vacancies in the O2-sensing mechanism of SnO2. Issue 20 (10th May 2022) - Kucharski, Stefan; Ferrer, Pilar; Venturini, Federica; Held, Georg; Walton, Alex S.; Byrne, Conor; Covington, James A.; Ayyala, Sai Kiran; Beale, Andrew M.; Blackman, Chris
Abstract : NAP-XPS characterisation of SnO2 under operando conditions shows that resistance change, band bending and surface O-vacancy concentration are correlated with ambient O2 concentration, challenging current preconceptions of gas sensor function. Abstract : Conductometric gas sensors (CGS) provide a reproducible gas response at a low cost but their operation mechanisms are still not fully understood. In this paper, we elucidate the nature of interactions between SnO2, a common gas-sensitive material, and O2, a ubiquitous gas central to the detection mechanisms of CGS. Using synchrotron radiation, we investigated a working SnO2 sensor under operando conditions via near-ambient pressure (NAP) XPS with simultaneous resistance measurements, and created a depth profile of the variable near-surface stoichiometry of SnO2− x as a function of O2 pressure. Our results reveal a correlation between the dynamically changing surface oxygen vacancies and the resistance response in SnO2 -based CGS. While oxygen adsorbates were observed in this study we conclude that these are an intermediary in oxygen transport between the gas phase and the lattice, and that surface oxygen vacancies, not the observed oxygen adsorbates, are central to response generation in SnO2 -based gas sensors.